Original paperHead and neck 192Ir HDR-brachytherapy dosimetry using a grid-based Boltzmann solver - Siebert, Frank-André; Wolf, Sabine; Kóvacs, George (Journal of Contemporary Brachytherapy, 2013)
Purpose: To compare dosimetry for head and neck cancer patients, calculated with TG-43 formalism and a commercially available grid-based Boltzmann solver. Material and methods: This study included 3D-dosimetry of 49 consecutive brachytherapy head and neck cancer patients, computed by a grid-based Boltzmann solver that takes into account tissue inhomogeneities as well as TG-43 formalism. 3D-treatment planning was carried out by using computed tomography. Results: Dosimetric indices D 90 and V 100 for target volume were about 3% lower (median value) for the grid-based Boltzmann solver relative to TG-43-based computation (p < 0.01). The V150 dose parameter showed 1.6% increase from grid-based Boltzmann solver to TG-43 (p < 0.01). Conclusions : Dose differences between results of a grid-based Boltzmann solver and TG-43 formalism for high-dose-rate head and neck brachytherapy patients to the target volume were found. Distinctions in D 90 of CTV were low (2.63 Gy for grid-based Boltzmann solver vs. 2.71 Gy TG-43 in mean). In our clinical practice, prescription doses remain unchanged for high-dose-rate head and neck brachytherapy for the time being.